The discovery of the genus Guaygata Marsh (Hymenoptera, Braconidae, Doryctinae) from China, with description of a new species - Tang, Pu; Belokobylskij, Sergey; Chen, Xue-Xin (Zootaxa, 2013)
The genus Guaygata Marsh, 1993 is recorded from China for the first time. Two species, i.e. G. mariae (Belokobylskij, 1993) and G. fujianensis sp. nov., are recognized. The new species is fully described and illustrated. A key to Asian species of Guay-gata is provided.